Investigating the Ameliorative Effects of Various Doses of Cerium Dioxide on Adult Male Rates in Comparison to Acrylamide Toxic Effect - Mohammed A. Qathee; Salema Lafta Hassan (International Journal of Medical Toxicology and Legal Medicine, 2025)
Acrylamide one of most popular exposure chemicals which cause several pathological alterations involving liver through depletion of GSH and elevation of MDA. Giving of Cerium dioxide which has antioxidant and anti-inflammatory properties.Is expected to improved biochemical parameters and protect cell from oxidative stressinjury.This experiment aims to limitation of acrylamide exposure effect by using suitable dose of cerium dioxide.In current study 120 mature male rat are used were divided randomly for 6 groups, each one consistsfrom 20 animals. And they were consecutively: ACR (8 mg/kg), ACR +Ceo2 (8 and 35mg/kg), ACR +Ceo2 (8 and 15mg/kg), Ceo2(35mg/kg), Ceo2(15mg/kg), and D.W. group. Daily dosing for 100 days. Finally, the liver samples were collected for biochemical, histopathological and immunohistochemistry investigations.This study revealed significant elevation of oxidative stress with acrylamide treated group. Where MDA elevation and GSH diminished. With high dose of cerium dioxide treated groups show significant decrease in MDA level and significant elevation level of GSH, disappearance of inflammation and elevation of anti-apoptoticprotein expression. The ameliorative effect of cerium dioxide appears with high dose (35mg/kg)when compared with acrylamide treated group.